Leveraging ICT to Enable Value Addition and Comprehensive Value Chain Participation for Smallholder Farmers in Kigezi Region: A Case Study of Potato Growers - Byamukama Mpora, Eliab; Sunday,Arthur; Mugalul,George; Turyahebwa,Abanis; Kaaya, Siraj; Turyasingura, Benson; Nakero, Sarah (International Journal of Research in Sociology and Anthropology (IJRSA), 2025)
The study of economic development and the well-being of smallholder potato growers in the Kigezi region was illustrated well to the benefit of readers and the magnitude of the outcome. The study was guided by the following objectives, identifying the main ICT technologies used within the agriculture domain; estimating the value addition of potatoes at different stages in the potato supply chain; identifying the constraints and opportunities in the potato supply chain, and recommending measures for improvement. The study adopted a cross-sectional survey research design, utilizing both quantitative and qualitative approaches. Using simple random and cluster sampling techniques, a total of 285 respondents were selected to participate in the study. The findings reveal varying levels of ICT adoption across the Kigezi region and on value adding the study revealed increasing engagement in direct sales, which could foster stronger market linkages and improve profitability. The constraints limiting ICT adoption among farmers were limited access to affordable internet and low levels of digital literacy among farmers. The regression analysis highlighted significant factors influencing ICT adoption among smallholder farmers. Age (Adjusted R² = 0.713) affected tailored information access; farm size (Adjusted R² = 0.697) impacted ICT infrastructure access; and digital literacy (Adjusted R² = 0.527) with the age. Cost perceptions were influenced by farm size (Adjusted R² = 0.8701), stressing the need for age-inclusive solutions, infrastructure investment, and affordable ICT tools for small farmers. The study highlighted the need for the government of Uganda, in collaboration with the institutions of higher learning, to design digital platforms that cater to diverse age groups, ensuring usability and relevance for younger and older farmers.